Biophysical mechanisms of the formation of wound channels in non-penetrating gunshot craniocerebral wounds - A.O. Danchyn (NAMS of Ukraine, State Organization "Scientific-Practical Center of Endovascular Neuroradiology, Non-Governmental Organization “All Ukrainian Association of Endovascular Neuroradiology, Shupyk National Healthcare University of Ukraine, 2021)
Objective ‒ to develop recommendations for optimization of primary surgical treatment of gunshot penetrating craniocerebral wounds on the basis of theoretical and applied study of one of the sections of wound ballistics ‒ biophysical mechanisms of wound canal formation, concomitant impenetrable wounds and intracranial injuries. Materials and methods. The medical histories of 155 wounded who received a non-pe- netrating craniocerebral injury during the hostilities in the East of Ukraine in 2014‒2020 were studied. All of the wounded were males between 18 and 60 years old (mean age ‒ 35.1 years). To study the biophysical features of the formation of different types of wound canals at a given non-lethal kinetic energy transferred to the head tissues, the type of the wounding projectile, the flight trajectory, the nature of gunshot injuries to the soft tissues of the cranial vault and skull fractures and intracranial injuries were determined according to the data of clinical stu- dies and computed tomography and compared with the results of theoretical studies using the laws of wound ballistics. Results. There were 11 (7.1 %) bullet (only tangential) wounds, and 144 (92.9 %) shrapnel. The formation of wound channels depends on the type of the wounding projectile and its kinetic energy. Non-penetrating firearms bullet and shrapnel tangential craniocerebral wounds are caused by the destructive effect of injuring shells on the tissues, which at the moment of collision with the head have both destructive kinetic energy (>80 J) and less than destructive kinetic energy. Blind craniocerebral injuries are caused only by the traumatic effects of fragments with a small (<80 J) kinetic energy. Conclusions. With gunshot non-penetrating single shrapnel blind wounds, the wounds do not have a zone of secondary necrosis, and the zone of primary necrosis is small or insignificant, which makes it possible not to carve soft tissues around the wound during primary surgical treatment, but only to remove necrotic tissues. With gunshot non-penetrating shrapnel tangential and blind craniocerebral wounds, when the soft tissue wounds of the cranial vault do not gap, small size (damage to the skin, subcutaneous tissue to aponeurosis), primary surgical treatment is not performed. Such wounds are treated with a toilet and aseptic dressings. Wound canals ending in gunshot fractures are subject to primary surgical treatment in the same way as gunshot fractures.